Minimising food waste: a call for multidisciplinary research - Alamar, M. Carmen; Falagán, Natalia; Aktas, Emel; Terry, Leon A. (Wiley, 2017)
Food losses and waste has always been a significant global problem for mankind, and one which has become increasingly recognised as such by policy makers, food producers, processors, retailers, and consumers. It is however an emotive subject whereby the extent, accuracy, and resolution of available data on postharvest loss and waste is questionable such that key performance indicators on waste can be misinformed. The nature and extent of food waste differs amongst developed economies, economies in transition, and developing economies. Whilst most emphasis has been put on increasing future crop production, far less resource has been and is still channelled towards enabling both established and innovative food preservation technologies to reduce food waste while maintaining safety and quality. Reducing food loss and waste is a more tractable problem than increasing production in the short to medium term, as its solution is not directly limited, for instance, by available land and water resources. Here we argue the need for a paradigm shift of current funding strategies and research programmes which will encourage the development, implementation, and translation of collective biological, engineering, and management solutions to better preserve and utilise food. Such cross disciplinary thinking across global supply chains is an essential element in the pursuit of sustainable food and nutritional security. The implementation of allied technological and management solutions is reliant on there being sufficient skilled human capital and resource. There is currently a lack of robust postharvest research networks outside of the developed world, and insufficient global funding mechanisms which can support such interdisciplinary collaborations. There is thus a collective need for schemes which encourage inter-supply chain research, knowledge exchange and capacity building to reduce food losses and waste.
Keywords: Postharvest loss; sustainability; food security; fresh produce